Driver Drowsiness Detection Using Wearable Pulse Sensor - Za’im, Muhammad Hafizuddin (Universiti Teknologi PETRONAS, 2020)
Driving is an everyday routine for most of the people nowadays regardless of genders and ages from teenager to old. Driving a vehicle require user to always aware and focus to their surroundings, a little mistake can cause a major accident. Drowsiness is a near sleep state that often happened to drivers due to body fatigue and the needs of rest will trigger this condition. According to Foundation for Traffic Safety, around 328,000 accidents annually due to fatigued drivers, of which 6,400 are fatal and 109,000 lead to injury and the true tally of drowsy driving is believed to be 350% higher than reported. As the numbers of accidents caused by drowsy driving are rather alarming, researcher and car developer decided to take this matter seriously and the technology to detect driver drowsiness based on vehicle and vital signals is being studied in preventive car safety. This paper will propose a drowsy detection system using heart rate as the input data to be extracted by using Photoplethysmography sensor that can be found in nowadays common wearable. The wearable IOT function and the comfortability while driving making it the best choice to suit the present.